PENGARUH DESAIN PRODUK DAN HARGA KOMPETITIF TERHADAP KEPUTUSAN PEMBELIAN DENGAN KEPERCAYAAN SEBAGAI VARIABEL MEDIASI - Umar Zaelani Sidiq; Marjam Desma Rahadhini; Sumaryanto Sumaryanto (Universitas Slamet Riyadi, 2020)
The purpose of this study is to analysis the effect of product design and competitive prices on consumer trust, analysis the effect of product design and competitive prices on purchasing decisions, analysis the influence of consumer trust on purchasing decisions and analysis consumer trust in mediating the effect of product design and competitive prices on purchasing decisions. Type of this research is a survey consumers of UD. Yoso Jati. The sampling technique using non probability sampling techniques with an accidental sampling method of 70 respondents. The technique of data collection by questionnaires, literature studies and observation. Data analysis techniques using multiple linear regression analysis and Sobel test. The result of the study indicated that the product design and competitive prices have an effect on consumer trust, product design and competitive prices have an effect on purchasing decisions, consumer trust influences purchasing decisions, consumer trust in mediating the effect of product design on purchasing decisions, consumer trust does not mediate the effect of competitive prices on purchasing decisions